Law and legitimacy in the Supreme Court - Fallon, Richard H., Jr., 1952- (The Belknap Press of Harvard University Press, 2018)
"The book addresses questions about the roles of law and politics and the challenge of legitimacy in constitutional adjudication in the Supreme Court. With all sophisticated observers recognizing that the Justices' political outlooks influence their decision making, many political scientists, some of the public, and a few prominent judges have become Cynical Realists. In their view Justices vote based on their policy preferences, and legal reasoning is mere window-dressing. This book rejects Cynical Realism, but without denying many Realist insights. It explains the limits of language and history in resolving contentious constitutional issues. To rescue the notion that the Constitution is law that binds the Justices, the book provides an original account of what law is and means in the Supreme Court. It also offers a theory of legitimacy in Supreme Court adjudication. Given the nature of law in the Supreme Court, we need to accept and learn to respect reasonable disagreement about many constitutional issues. If so, the legitimacy question becomes: how would the Justices need to decide cases so that even those who disagree with the outcomes ought to respect the Justices' processes of decision? The book gives a fresh and counterintuitive answer to that vital question. Adapting a methodology made famous by John Rawls, it argues that the Justices should strive to achieve a "reflective equilibrium" between their interpretive principles, framed to identify the Constitution's enduring meaning, and their judgments about appropriate outcomes in particular cases, evaluated as prescriptions for the nation to live by in the future. The book blends the perspectives of law, philosophy, and political science to answer theoretical and practical questions of pressing national importance"--